2021
DOI: 10.1044/2021_jslhr-20-00251
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Age, Working Memory Capacity, and Inhibitory Control on Speech Recognition in Noise in Young and Older Adult Listeners

Abstract: Purpose The study aimed to investigate the relationship between speech recognition in noise, age, hearing ability, self-rated listening effort, inhibitory control (measured with the Swedish Hayling task), and working memory capacity (WMC; measured with the Reading Span test). Two different speech materials were used: the Hagerman test with low semantic context and Hearing in Noise Test sentences with high semantic context, masked with either energetic or informational maskers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…For instance, Desjardins and Doherty (2013) showed that listening effort was significantly negatively correlated with working memory capacity (WMC) and processing speed. Similarly, Stenbäck et al (2021) found a negative relation between subjectively assessed listening effort and WMC, in line with the view that larger cognitive capacity is associated with less effort. However, it should be noted that such an association was not found in all studies (cf.…”
Section: Introductionsupporting
confidence: 83%
“…For instance, Desjardins and Doherty (2013) showed that listening effort was significantly negatively correlated with working memory capacity (WMC) and processing speed. Similarly, Stenbäck et al (2021) found a negative relation between subjectively assessed listening effort and WMC, in line with the view that larger cognitive capacity is associated with less effort. However, it should be noted that such an association was not found in all studies (cf.…”
Section: Introductionsupporting
confidence: 83%
“…The main result of the current study supports the notion that cognitive functioning is important for listening in adverse conditions, regardless of hearing status. Importantly, we found that cognitive functioning is crucial at 50% word recognition, whereas a lot of research has shown effects at 80% word recognition, or higher, SRT (e.g., Larsby et al 2011; Stenbäck et al 2015, 2016). That cognitive processes are crucial for adverse listening conditions is further in line with the ELU model (e.g., Rönnberg et al 2013, 2019).…”
Section: Discussionmentioning
confidence: 54%
“…A majority of the research has examined the effects of cognition in groups of people with hearing loss (e.g., Arehart et al 2013;Foo et al 2007;Lunner 2003). This relationship has also been found in young normal-hearing persons in some studies (e.g., Michalek et al 2018;Stenbäck et al 2015Stenbäck et al , 2021 and older normal-hearing (Füllgrabe et al 2015). Here, we extend this research by using statistical techniques that enable us to model this and compare the effects between groups (i.e., normal-hearing and hearingimpaired older individuals).…”
Section: Discussionmentioning
confidence: 90%
“…In further support of the inhibition component, recent studies by Stenbäck et al (2015Stenbäck et al ( , 2021 verify that especially WMC (measured with the RST) but also the Swedish Hayling test (Stenbäck et al, 2015), which measures inhibition, were significant predictors of performance in speech-innoise (SPIN, Hällgren et al, 2006) and Hagerman matrix sentences (Hagerman, 1982). The Hayling test builds on the ability to inhibit sentence completion of the last semantically correct word instead of providing a semantically incorrect but grammatically correct word.…”
Section: Output From the Elu Systemmentioning
confidence: 90%